Electrical breakdown of suspended mono- and few-layer tungsten disulfide via sulfur depletion identified by in situ atomic imaging - Fan, Y; Robertson, A; Zhou, Y; Chen, Q; Zhang, X; Browning, N; Zheng, H; Rümmeli, M; Warner, J (American Chemical Society, 2017)
The high-bias and breakdown behavior of suspended mono- and few-layer WS2 was explored by in situ aberration-corrected transmission electron microscopy. The suspended WS2 devices were found to undergo irreversible breakdown at sufficiently high biases due to vaporization of the WS2. Simultaneous to the removal of WS2 was the accompanying formation of few-layer graphene decorated with W and WS2 nanoparticles, with the carbon source attributed to organic residues present on the WS2 surface. The breakdown of few-layer WS2 resulted in the formation of faceted S-depleted WS2 tendrils along the vaporization boundary, which were found to exhibit lattice contraction indicative of S depletion, alongside pure W phases incorporated into the structure, with the interfaces imaged at atomic resolution. The combination of observing the graphitization of the amorphous carbon surface residue, W nanoparticles, and S-depleted WS2 phases following the high-bias WS2 disintegration all indicate a thermal Joule heating breakdown mechanism over an avalanche process, with WS2 destruction promoted by preferential S emission. The observation of graphene formation and the role the thin amorphous carbon layer has in the prebreakdown behavior of the device demonstrate the importance of employing encapsulated heterostructure device architectures that exclude residues.